Resource Potential Analysis of Pyrite Tailings in Linkou Area of Bijie, Guizhou Province - Baichuan SUN; Ruidong YANG; Chaokun LUO; Xinzheng LI (Kuangchan zonghe liyong)
Pyrite tailings in sulfur mining area are the main solid wastes, which not only take up a lot of land resources, but also have an impact to the environment. Linkou area in Bijie, northwest Guizhou, has a history of several decades of sulfur refining using the local method, and a large amount of sulfurous iron ore tailings have been piled up, and the analysis of the data and the field survey found that 73,357,200 t of sulfurous iron ore tailings are piled up at present. The main trace and rare earth elements (REE) of pyrite tailings in this area were tested by using the method of tailing geochemical exploration. It was found that TFe, Ti, V and REY in pyrite tailings have reached the boundary grade, which has potential utilization value. Through X-ray diffraction (XRD) and scanning electron microscope (SEM) tests, it is found that the minerals of pyrite tailings in this area are mainly quartz and hematite, and the content of TFe is 21.36% ～38.36%, which is equivalent to piling up a large hematite deposit, and has a good utilization prospect. Combined with the relevant literature, the paper puts forward to some suggestions for the comprehensive utilization of pyrite tailings in this area. The study has certain reference significance for the comprehensive utilization of the same type of mine tailings.